2016
DOI: 10.1002/oby.21685
|View full text |Cite
|
Sign up to set email alerts
|

Perceived weight status and weight change among a U.S. adult sample

Abstract: Objectives Examine bi-directional associations between weight perception and weight change over time among adults. Methods Data are from adult employees (N=623) across 12 U.S. public high schools participating in a cluster-randomized multilevel weight gain prevention intervention. Data were collected at baseline, 12 months, and 24 months. Perceived weight status (very/somewhat underweight, just right, somewhat overweight, very overweight) were obtained via self-administered surveys. Weight (kg) was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Overall, there was strong evidence to suggest that individuals who perceived themselves as overweight were more likely to gain weight over time than those who perceived themselves as normal weight across most participant subgroups. Results of a supplementary analysis of a subset of nine studies that assessed weight change using objectively measured BMI only (i.e. those that met quality criterion 8; Table S4a) were consistent with the main evidence synthesis: there was strong evidence to indicate that overall, perceived overweight was associated with weight gain over time.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Overall, there was strong evidence to suggest that individuals who perceived themselves as overweight were more likely to gain weight over time than those who perceived themselves as normal weight across most participant subgroups. Results of a supplementary analysis of a subset of nine studies that assessed weight change using objectively measured BMI only (i.e. those that met quality criterion 8; Table S4a) were consistent with the main evidence synthesis: there was strong evidence to indicate that overall, perceived overweight was associated with weight gain over time.…”
Section: Resultssupporting
confidence: 62%
“…Initial database searches identified 10,398 unique records, and an additional 41 articles were identified by authors, from the reference lists of eligible articles or from supplementary searches. Full‐text review of 366 articles was completed, and 74 articles (indicated with asterisks in reference list) that described 78 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift could be linked to a potential reevaluation of their goals, as individuals may perceive themselves as more capable and motivated to reduce their silhouette. 25,26 Previous research has associated physical exercise with an enhancement in the perception of competence among adults with obesity, referring to an individual's belief in their ability to accomplish tasks or activities. 27 This surge in perceived competence is intertwined with intrinsic motivation, stemming from the personal satisfaction derived from engaging in an activity.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of weight was measured by a single question. Women were asked to think about how much they weight and if they considered themselves “very overweight”, “moderately overweight”, “a little overweight”, “just right”, “a little underweight”, “moderately underweight”, or “very underweight” [18].…”
Section: Methodsmentioning
confidence: 99%